In vitro evaluation of Cordyceps bassiana (Ascomycota: Sordariomycetes) in the biological control of Rhipicephalus microplus - García-Corredor, Diego José (2016)
The aim of the present study was to evaluate the in vitro efficacy of Cordyceps bassiana for the control of the adult stage of Rhipicephalus microplus. The adult immersion test in a solution containing the BbF2011 strain of C. bassiana at the concentrations of 1x104, 1x106 and 1x108 conidia/ml (30 ticks per treatment) was evaluated. Treated ticks at a concentration of 1x108 conidia/ml reached 100% mortality at 15 days post-treatment (PT), while ticks at concentrations of 1x106 y 1x104 conidia/ml reached it at 18 and 21 days PT, respectively. Tick mortality was directly related to the fungi concentration. Moreover, ticks at the concentration 1x108 conidia/ml showed the lowest oviposition and larva hatching as compared to 1x106 and 1x104 conidia/ml concentrations (p<0.05). The effectiveness shown by C. bassiana on R. microplus opens the option to a new biological control method.